Menyelaraskan Kebijakan dan Sistem Manajemen Hutan Ramin (Gonystylus spp.) untuk Perbaikan Ekosistem Rawa Gambut di Indonesia - Marcellinus Mandira Budi Utomo (ULIN: Jurnal Hutan Tropis, 2020)
Recently, Indonesian peatland has become global attention regarding several forest fire events, which are seemingly caused by the improper ecosystem management system. Through literature review, this paper discusses one of specific forest formations in peat swamp, namely ramin forest (Gonystylus spp.). An assessment is performed for ramin forest management system from time to time using a framework developed by Indonesian Eco-Labelling Organisation. The criteria applied are sustainability of production, ecological, and social functions. Several recommendation to refine ramin forests are (1) assure new concession permit in any peat swamp areas stops and (2) hasten the implementation of one-map policy as a baseline for further planning and calculating current potency of ramin. For the new regulation, activities can be carried out are (1) to rehabilitate the degraded peat-peat swamp forests, (2) to strictly protect the last pristine ramin forests, (3) to establish seed orchard from seed resources to conserve the germ plasma, (4) to support research into ramin degraded forest restoration and the ecological relationship in pristine ramin forests to better understand how the system works, (5) to recalculate the current diameter increment and to use that to calculate the harvesting rotation, and (6) to uphold forestry law more firmly.